2017
DOI: 10.1097/mat.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Biological Effects of Long-Acting Octreotide in Patients With Continuous Flow Left Ventricular Assist Devices

Abstract: Patients with implanted continuous, nonpulsatile, left ventricular assist devices (LVADs) have increased the occurrence of gastrointestinal bleeding (GIB). Although the pathophysiology is multifactorial, there are few treatments beyond supportive care. Octreotide acetate is a somatostatin analog that reduces GIB in various patient populations. However, there are sparse case series that suggest octreotide acetate may reduce GIB in LVAD patients. This 10 patient, 28 week phase I study evaluated the safety and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Therefore, the risk for GI bleeding among patients in that study may not be as high as our patients. 15 In our cohort, three patients experienced pump thrombosis during octreotide therapy, possibly related to inability to maintain therapeutic anticoagulation levels due to recurrent GI bleeding.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, the risk for GI bleeding among patients in that study may not be as high as our patients. 15 In our cohort, three patients experienced pump thrombosis during octreotide therapy, possibly related to inability to maintain therapeutic anticoagulation levels due to recurrent GI bleeding.…”
Section: Discussionmentioning
confidence: 88%
“…22, 23 Measurement of GI bleeding-associated factors such as vascular endothelial growth factor and portal vein pressure before and during octreotide therapy may also be useful for optimal patient selection. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a case by case basis, success with octreotide - a somatostatin analogue which acts as a splanchnic vasoconstrictor and may affect angiogenesis - has been reported[64], but its application to control bleeding and prevent future hemorrhages in LVAD patients may be offset by high cost and limited outpatient use[11]. Recent small phase I trial showed octreotide potential effectiveness and general tolerability as early intervention[65] and future large prospective randomized investigations would be necessary to further define its role in LVAD population. There was anecdotal use of antihemophilic factor/vWF complex and hormonal (estrogen, desmopressin) therapy in refractory bleeding[35,66], although unclear if the patient would have benefited from repeated small intestinal evaluation prior to its initiation.…”
Section: Managementmentioning
confidence: 99%
“…[13][14][15][16] A recent prospective study was conducted with octreotide in stable LVAD patients and was noted to be well tolerated with no drug-related side effects or GI bleeding events observed. 17 To further elucidate the potential role of octreotide in preventing recurrent LVAD-associated GI bleeding, we conducted a retrospective, multicenter cohort study to determine the incidence of rebleeding in patients receiving secondary octreotide prophylaxis. Herein, we report the demographics and clinical characteristics associated with rebleeding versus non-rebleeding and further compare these data to a historical control group comprised patients who experienced GI bleeding in the original clinical trial of the HMII (HeartMate II) LVAD.…”
mentioning
confidence: 99%